Does Trade Integration Contribute to Peace?. Issue 1 (February 2016) - Lee, Jong‐Wha; Pyun, Ju Hyun
Abstract: We investigate the effect of trade integration on interstate military conflict. Our empirical analysis, based on a large panel data set of 243, 225 country‐pair observations from 1950 to 2000, confirms that an increase in bilateral trade interdependence significantly promotes peace. It also suggests that the peace‐promotion effect of bilateral trade integration is significantly higher for contiguous countries that are likely to experience more conflict. More importantly, we find that not only bilateral trade but global trade openness also significantly promotes peace. It shows, however, that an increase in global trade openness reduces the probability of interstate conflict more for countries far apart from each other than it does for countries sharing borders. The main finding of the peace‐promotion effect of bilateral and global trade integration holds robust when controlling for the simultaneous determination of trade and peace.